Renewable energy supply chain in Malaysia: Fostering energy management practices and ecological performance - Al-Madani, Mohammed Hammam Mohammed; Fernando, Yudi; Iranmanesh, Mohammad; Lim, Ming K.; Tseng, Ming-Lang (Elsevier, 2024)
The trade-off between environmental issues and economic outcomes has challenged manufacturing firms to manage the renewable energy supply chain (RESC). The Malaysian manufacturing industry has been challenged for its capacity to contribute to renewable energy development and reliance on imported components. The renewable energy supply chain has risks for uncertainty, higher costs, longer lead times, and disruption. Prior studies uncover the impact of fostering energy management practices (EMPs) and ecological performance (EC) in the renewable energy supply chain under a natural resource-based view (RBV). The government has provided the incentive to drive the successful implementation of energy management to obtain clean energy and business sustainability. This study contributes to developing a theoretical model that examines the intervening effect of the RESC on EMPs and EC. This study analysed the responses of 129 manufacturing firms to understand energy management practices. The findings show that energy auditing positively relates to RESC and that government incentives have impacted energy management practices. Management commitment and energy knowledge directly affected manufacturing firms’ ecological performance. The results show that manufacturing firms can best design energy management, green strategy, and competitiveness for business sustainability. Theoretical, policy and managerial implications are discussed.